Civility in the Enchanted City: The Malfūzāt of Ḥażrat Niẓāmuddīn Awliyā’ - S. Razi Shaikh (Tasavvuf Araştırmaları Enstitüsü Dergisi)
Civility has been variously described as a social norm, an attitude, even a virtue. The wide variety of ascriptions attached to it indicate as much its versatility as its indispensability for the construction of a sustainable society. Yet how widespread is civility, across history and societies? This is a question that attempts to wean the concept off its often-Eurocentric conceptualization, wherein civility was tied to the ‘civilizing process’ described and championed by Norbert Elias. This article undertakes a study of civility in a very different social context, by zooming onto the Chishti khānqāh of Ḥażrat Niẓāmuddīn Awliyā’ in early thirteenth century India. The underlying contention is that civility in this milieu was expressed through the key Sufi vocabulary of adab, futuwwa and gharib nawazi, it was not tied to the civilizing process of a Leviathan State. Rather, it was the individual moral self, trained and elevated by a charismatic Shaykh, aided by the comradeship of the khānqāh, and grounded in a world that was resolutely ‘enchanted’ that made the acquisition and solidification of civility a feasible process. This article seeks a sociological examination of that project.